TRANSIENT STABILITY ANALYSIS WITH CRITICAL CLEARING TIME METHOD ON TRANSMISSION LINE 150 KV - Rahmaniar, Rahmaniar; Wibowo, Pristisal; Br Meliala, Paulina Magdalena (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
Transient stability is the ability of the power system to maintain synchronism when subjected to a transient disturbance such as a fault on a transmission line. To obtain the stability condition of the power system after fault, a transient stability study must be done. This research applies to transmission line fault and analyses its effect on Critical Clearing Time. This research will determine Critical Clearing Time in each fault condition and carried out with Runge-Kutta 4 th Order Method and applied in computing software Matlab R2015a using 5 Busses and 2 Machines system. This research contains 5 case conditions. The result of the simulation show that 1 st case cleared at 0.29 second, 2 nd case cleared at 0.38 second, 3 rd the case cleared at 0.22 second, however, the 4 th and 5 th case show that the system remain stable along the fault. The stability condition is affected by the location of the fault, load factor, and influence of reactances in power system lines. Small load factors have a great Critical Clearing Time and the number of line reactances will affect received electric power transfer to become smaller.